Transcriptomic and metabolomic analysis of recalcitrant phosphorus solubilization mechanisms in Trametes gibbosa - Chen, Yulan; Farooq, Akasha; Wei, XieLuyao; Qin, Leitao; Wang, Yong; Zhang, Lingzi; Xiang, Quanju; Zhao, Ke; Yu, Xiumei; Chen, Qiang; Gao, Xue; Nyima, Tashi; et al. (Frontiers in Microbiology, 2025)
IntroductionPhosphorus (P) is a crucial growth-limiting nutrient in soil, much of which remains challenging for plants to absorb and use. Unlike chemical phosphate fertilizers, phosphate-solubilizing microorganisms (PSMs) offer a means to address available phosphorus deficiency without causing environmental harm. PSMs possess multiple mechanisms for phosphorus solubilization. Although the phosphorus-solubilizing mechanisms of phosphate-solubilizing bacteria (PSB) have been well characterized, the mechanisms utilized by phosphate-solubilizing fungi (PSF) remain largely unexplored.MethodsThis study isolated a PSF strain, Trametes gibbosa T-41, from soil and evaluated its phosphorus solubilizing capacity with organic (calcium phytin; Phytin-P) and inorganic (tricalcium phosphate; Ca-P) phosphorus sources. The phosphorus solubilization, enzyme activity, and organic acid production of T-41 were measured. And the P-solubilizing mechanism conducted by transcriptomic and metabolomic analyses.Results and discussionT-41 exhibited varying phosphorus solubilizing capacity when grown with organic (calcium phytin; Phytin-P) and inorganic (tricalcium phosphate; Ca-P) phosphorus sources (109.80 ± 8.9 mg/L vs. 57.5 ± 7.9 mg/L, p < 0.05). Compared with the Ca-P treatment, T-41 demonstrated a stronger alkaline phosphatase (ALP) production capacity under Phytin-P treatment (34.5 ± 1.2 μmol/L/h vs. 19.8 ± 0.8 μmol/L/h, p < 0.05). Meanwhile, the production of oxalic acid, maleic acid, and succinic acid was higher under Phytin-P treatment (p < 0.05). Transcriptomic and metabolomic analysis revealed that different phosphorus sources altered metabolic pathways such as galactose metabolism, glyoxylate and dicarboxylic acid metabolism, and ascorbate and aldolate metabolism. Key metabolites like myo-inositol, 2-oxoglutarate, and pyruvate were found to impact the performance of T. gibbosa T-41 differently under the two P sources. Notably, synthesis in Ca-P vs. Pytin-P, T-41 upregulated genes involved in myo-inositol synthesis, potentially enhancing its P-solubilizing ability. These results provide new insights into the molecular mechanisms of PSF at the transcriptomic and metabolomic levels, laying a theoretical foundation for the broader application of PSF as bio-phosphorus fertilizers in the future.